2017
DOI: 10.1007/s10072-017-3146-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of severe neurosurgical patients with pyogenic ventriculitis caused by gram-negative bacteria

Abstract: The aim of the study is to explore the experiences in diagnosis and treatment of severe neurosurgical patients with pyogenic ventriculitis caused by gram-negative bacteria (G). Nineteen patients with pyogenic ventriculitis were reviewed for their treatment. The bacterial testing results of cerebrospinal fluid (CSF), the clinical intervention, and the patients' prognosis were evaluated. The bacterial smears of ventricular drainage from all the cases were G bacteria. Head CT and MRI scans confirmed that they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…According to reports, the mortality rate associated with intracranial infections caused by MDR/XDR G-bacilli is as high as 26-71%. [22][23][24] The total mortality rate in this study was 17.6% (5/28), and the mortality rate directly caused by infection was 7.1% (2/28), which was lower than that reported in the literature. This may be related to the timely use of intraventricular polymyxin B following the identification of MDR/XDR G-bacilli in the patients in this study.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…According to reports, the mortality rate associated with intracranial infections caused by MDR/XDR G-bacilli is as high as 26-71%. [22][23][24] The total mortality rate in this study was 17.6% (5/28), and the mortality rate directly caused by infection was 7.1% (2/28), which was lower than that reported in the literature. This may be related to the timely use of intraventricular polymyxin B following the identification of MDR/XDR G-bacilli in the patients in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, Shang et al reported that intraventricular lavage combined with daily polymyxin E can effectively improve the neurological symptoms and CSF laboratory indicators in patients with severe ventricular inflammation. 22 In this study, intraventricular polymyxin B has also been used to achieve the same effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies have found that timely intervention in hydrocephalus can help patients to achieve better prognosis because hydrocephalus secondary to purulent infection contains viscous pus that affect the concentration of antibiotics in the ventricular system and thus affecting the treatment outcome. 7,8 Therefore, it is of great importance to determine the predicting factors of hydrocephalus in meningitis patients. To provide insights for early diagnosis and treatment of hydrocephalus, we conducted a single-center retrospective study to evaluate the risk factors for hydrocephalus in neonatal purulent meningitis and discuss the characteristics of the disease.…”
mentioning
confidence: 99%
“…[ 2 ] Clinically, most patients with ventriculitis present with fever, deterioration of the conscious level, and dysneuria. [ 3 ] Delayed in the diagnosis and treatment will lead to severe intracranial infection, serious neurological impairment, and death. Most cases of ventriculitis have been reported in the newborns and infants, with bacteria being the most common pathogens, although several cases of ventriculitis secondary to aspergillus fumigatus infection have been described.…”
mentioning
confidence: 99%